Sintesis Berkelanjutan Silika Xerogel (SiO2) dari fly ash: Optimasi Konsentrasi NaOH dan Waktu Aging menggunakan RSM - Alifea Arpy; Edi Nasra; M.Iqbal Saputra Gemasih; Afdila Nada (Lembaga Yasin AlSys, 2026)
Response Surface Methodology (RSM) was used to optimize the synthesis of silica xerogel from fly ash by evaluating the effects of NaOH concentration and aging time on xerogel mass as the main response. This study aimed to develop a statistical model capable of predicting and optimizing the process conditions for the synthesis of fly ash–based silica xerogel. A Central Composite Design (CCD) with 14 runs was applied to construct a quadratic regression model and analyze the relationships among process conditions. The statistical analysis showed that the quadratic model was significant (p < 0.05), with a coefficient of determination (R²) of 0.7515, indicating good agreement between the model predictions and the experimental data. The quadratic factors of NaOH concentration and aging time had significant effects on the response, indicating a nonlinear relationship and the presence of an optimum region, which was visualized through response surface and contour plots. Numerical optimization identified optimum conditions at an NaOH concentration of 8.5 M and an aging time of 17.89 hours, yielding a predicted xerogel mass of 0.388 g with a desirability value of 0.891. Confirmation tests demonstrated good agreement between the experimental results and model predictions, thereby confirming the effectiveness of RSM in optimizing the synthesis of silica xerogel from fly ash.